Landscapes and cities rural settlement and civic transformation in early imperial Italy - Patterson, John R.; Oxford eBooks (Oxford : Oxford University Press, 2006)
'Landscapes and Cities' investigates the relationships between city & countryside in Italy in the early Empire, using evidence from literary texts & inscriptions, & data derived from archaeological field surveys. This book examines how patterns of building in the cities were related to developments in the country.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Cities and towns, Ancient -- Italy, Central; Cities and towns, Ancient -- Italy, Southern; Cities and towns, Ancient -- Rome; Land settlement -- Italy, Central -- History; Land settlement -- Italy, Southern -- History; Urbanization -- Rome; Rome -- History -- Empire, 30 B.C.-476 A.D.; Rome -- Social conditions; Italy -- Antiquities, Roman; Electronic books